Mechanistic insights into the pleiotropic effects of butyrate as a potential therapeutic agent on NAFLD management: A systematic review - Amiri, Parichehr; Arefhosseini, Sara; Bakhshimoghaddam, Farnush; Jamshidi Gurvan, Hannah; Hosseini, Seyed Ahmad (Frontiers in Nutrition, 2022)
Non-alcoholic fatty liver disease (NAFLD) is one of the most common chronic diseases worldwide. As a multifaceted disease, NAFLD's pathogenesis is not entirely understood, but recent evidence revealed that the gut microbiota plays a significant role in its progression. Butyrate, a gut microbiota metabolite, has been reported to have hepato-protective effects in animal models of NAFLD. The purpose of this systematic review was to determine how butyrate affects the risk factors of NAFLD. Searches were conducted using relevant keywords in electronic databases up to March 2022. According to evidence presented in this study, butyrate contributes to a wide variety of biological processes in the gut-liver axis. It exerts beneficial properties such as improving intestinal homeostasis and liver health, anti-inflammatory, metabolism regulatory, and anti-oxidant effects. These effects may be attributed to butyrate's ability to regulate gene expression as an epigenetic modulator and trigger cellular responses as a signaling molecule. However, the exact underlying mechanisms remain unclear. Since no human trials have been performed on the effect of butyrate on NAFLD, there are concerns about whether the results of animal studies can be translated to humans. This review summarizes current knowledge about the properties of butyrate, particularly its potential effects and mechanisms on liver health and NAFLD management.